The Last Flight of Petr Ginz - Dickson, Sandy; Roberts, Churchill (United States, 2011)
Combining animation, art and live action, “The Last Flight of Petr Ginz” is a whimsical journey through a young boy's imagination. By age 14, Petr Ginz had written five novels and penned a diary about the Nazi occupation of Prague. By 16, he edited an underground magazine in the Theresienstadt Ghetto. This film is a testament to how creative expression represents the best of what makes us human, even in the darkest of times.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films